2018
DOI: 10.1136/openhrt-2017-000716
|View full text |Cite
|
Sign up to set email alerts
|

Changes in contractile protein expression are linked to ventricular stiffness in infants with pulmonary hypertension or right ventricular hypertrophy due to congenital heart disease

Abstract: BackgroundThe right ventricle (RV) is not designed to sustain high pressure leading to failure. There are no current medications to help RV contraction, so further information is required on adaption of the RV to such hypertension.MethodsThe Right Ventricle in Children (RVENCH) study assessed infants with congenital heart disease undergoing cardiac surgery with hypertensive RV. Clinical and echocardiographic data were recorded, and samples of RV were taken from matched infants, analysed for proteomics and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 33 publications
1
16
0
1
Order By: Relevance
“…While we have compared our data to transcript data from both mouse and human RVF, we acknowledge that this is not exhaustive and may describe specific rather than generic RV pathology and only at the transcript level. For example, comparison of our data with a recent proteomic analysis of RV from children with tetralogy of Fallot (TOF) [ 70 ] revealed only a small overlap between our data and theirs (17 proteins identified that have corresponding transcripts regulated in the rat MCT RV). While this paper also highlighted the significant enrichment of proteins involved in calcium signaling, our own functional analysis does not reveal this function as enriched.…”
Section: Discussionmentioning
confidence: 55%
“…While we have compared our data to transcript data from both mouse and human RVF, we acknowledge that this is not exhaustive and may describe specific rather than generic RV pathology and only at the transcript level. For example, comparison of our data with a recent proteomic analysis of RV from children with tetralogy of Fallot (TOF) [ 70 ] revealed only a small overlap between our data and theirs (17 proteins identified that have corresponding transcripts regulated in the rat MCT RV). While this paper also highlighted the significant enrichment of proteins involved in calcium signaling, our own functional analysis does not reveal this function as enriched.…”
Section: Discussionmentioning
confidence: 55%
“…Although authors have demanded that these changes are related to early RV response, they are more consistent with the alterations we have observed at the end stages of the disease. Interestingly, study by Bond et al showed abnormalities in the calcium signaling pathways of the RV myocardium in children with hypertensive RV, where increased expression of myocardial contractile and extracellular proteins was accompanied by enriched calcium signaling 51 . Same increase in RV structural and contractile proteins were observed in current study however downregulation of proteins related to cardiomyocyte Ca 2+ currents were noted.…”
Section: Discussionmentioning
confidence: 99%
“…Systolic heart failure is also known as heart failure with reduced ejection fraction (HFrEF) and occurs when a decreased force of contractility of the left ventricle reduces the pumping capacity. Diastolic dysfunction, also known as heart failure with preserved ejection fraction (HFpEF), occurs when the muscle in the left ventricle becomes stiff, due to either change in contractile proteins of cardiac myocytes or effect of fibrosis on relaxation [14]. Right heart failure occurs in association with lung disease leading to pulmonary hypertension and as an end stage of left ventricular failure [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that resident and recruited immune cells play a role in cardiac injury and are present in cardiac tissue early in disease [15, 9]. Initially, resident and infiltrating immune cells activate inflammatory/reparative pathways, and the relative balance between pathological inflammatory pathways and tissue reparative processes (physiological inflammation) defines the course of HF development [10].…”
Section: Introductionmentioning
confidence: 99%